EFEKTIVITAS FILM MOTIVASI UNTUK MENURUNKAN KECEMASAN PADA REMAJA YANG MENGHADAPI UJIAN SBMPTN - Yusmita Yusmita; Fitriatul Masruroh; Riza Faishol (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Anxiety is an unpleasant feeling of fear and worry that occurs in many psychopathologies and is a major aspect of many disorders. One of the methods used to reduce anxiety is the method of giving motivational films. This study aims to determine anxiety before watching motivational films and after watching motivational films as well as physical and psychological anxiety before watching movies and after watching films. The subjects in this study were prospective new students who came from organda (regional organization) Hipermata. The subjects were selected through non-random sampling with purposive sampling technique with 6 subjects. The research method used is experimental research using within subject design, namely one group pretest-posttest design. The measuring instrument used in this study was the pretest and posttest scales. The analysis technique used in this study is the Wilcoxon test using SPSS 22, which shows that the hypothesis is significant 0.014 <α 0.05, the hypothesis is accepted, so it can be concluded that anxiety before watching a motivational film is higher than after watching a motivational film